ANALISIS KEPEMIMPINAN, ETOS KERJA, DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KOPKAR PT GUDANG GARAM, TBK “MEKAR” KEDIRI - Putri, Arum Eka Refany; Muslih, Basthoumi; Soedjoko, Dodi Kusuma Hadi (Universitas Nusantara PGRI Kediri, 2022)
In the current era, companies need to improve employee performance qualifications in order to compete in increasingly fierce business competition. Employee performance is influenced by several factors that can influence it, including leadership, work ethic, and work discipline. This study aims to analyze the influence jointly or partially between leadership, work ethic and work discipline on employee performance at Kopkar PT Gudang Garam Tbk,